Neurocognitive and adaptive phenotypes in adolescent inpatients with mood disorders: an exploratory study on disruptive mood dysregulation disorder in the framework of depressive disorders - Apicella, Massimo; Pisa, Marcella Caterina; Averna, Roberto; Labonia, Milena; Pontillo, Maria; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Introduction Few studies on adolescents have investigated intelligence quotient (IQ) in mood disorders. Evidence on Disruptive Mood Dysregulation Disorder (DMDD), a controversial entity among depressive disorders, is more limited. Materials and methods We performed an exploratory study on adolescent inpatients with unipolar mood disorders to test specific impairment in cognitive and adaptive profile. We also considered common psychopathological comorbidities. We retrospectively collected data on inpatients with a diagnosis of major depressive disorder (MDD), DMDD or Depressive Disorder – Not Otherwise Specified (DD-NOS) evaluated with Wechsler Scales of Intelligence, Adaptive Behavior Assessment System (ABAS-II), and Children’s Global Assessment Scale (C-GAS). Results Out of 198 inpatients (85.9% females), 33.3% had MDD, 60.1% DD-NOS and 6.6% DMDD. DMDD patients had higher rates of ADHD (15.4%) and learning disorders (LD, 23.1%), a lower mean IQ (87.8 ± 10.7; p = 0.001) and ABAS-II scores (general composite 68.8 ± 16.8; p = 0.002) than other groups. In linear regression analysis, DMDD retained a significant correlation with lower IQ and adaptive abilities when controlling for sex, and comorbidities. Among comorbidities, LD correlated with lower perceptual reasoning and IQ, and ADHD with lower conceptual adaptive abilities. In all diagnosis groups, working memory and processing speed were lower than verbal comprehension and perceptual reasoning. Discussion While impairment in working memory and processing speed is a non-specific correlate of active mood disorder, DMDD is burdened by lower general intelligence and adaptive abilities and higher rate of neurodevelopmental comorbidities. Lower IQ in the normal range is a correlate of DMDD among variables examined, not explained by the effect of neurodevelopmental comorbidities. These findings are discussed with regards to possible implications for the consideration of DMDD as a bridge condition between neurodevelopmental disorders and mood disorders.